Implementation of the Basic Concept of Community-Centered Sustainability at the Pindang Center in Sudimara, Tabanan: Bahasa Indonesia - I Wayan, Selva Paryata; Nugraha, Putu Gede Wahyu Satya; Kurniawan , Agus; Wicaksana , Gde Bagus Andhika; Sari, Putri Ayu Devy Permata (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2025)
Pindang, as one of Bali’s strategic fishery commodities, has yet to be supported by proper architectural facilities. Current production areas are often located within residential neighborhoods, leading to pollution and limited accessibility. The existing buildings are generally simple, unsanitary, and lack efficient spatial organization in accordance with hygienic workflow standards.Therefore, the establishment of the Pindang Center in Sudimara Village, Tabanan, with a community-centered sustainability concept, aims to address these issues and support the development and continuity of the pindang industry, which represents a traditional fish preservation technique. The integration of this center with educational tourism serves to introduce traditional fish preservation methods and promote the benefits of fish consumption to the public—an effort to help address low fish consumption rates in the community.The research methodology includes data collection methods (literature review, field observation, interviews, and precedent studies), data presentation methods (descriptive narratives, tables, and visual documentation), and analytical methods (comparative analysis, general analysis, and synthesis). The research results in a design concept encompassing outdoor spatial planning, pindang processing facilities, and supporting utilities, placing pindang production activities at the core of architectural considerations in line with the fundamental concept of community-centered sustainability.